Metal complex derivatives of peptide nucleic acids (PNA) - Krämer, Roland; Mokhir, Andriy (Interplay between metal ions and nucleic acids, 2012)
Peptide nucleic acid (PNA) is a non-cyclic pseudopeptide-nucleic acid structural mimic with promising applications within diagnostics and drug discovery. This review focuses on metal complex derivatives of PNA. Metal ions and their complexes display unique physical and chemical properties and offer the opportunity to introduce new labels and probes for bioanalytical and diagnostic applications of PNA, but also to modulate or to introduce new (for example catalytic) functions and biological activities.
First online: 30 September 2011
Gesehen am 08.11.2018